Anaerobic threshold determination by direct blood lactate measurement without warm up protocol in female athletes - Mladenović-Ćirić Ivana B.; Jovanović Jelena V. (Srpsko lekarsko drustvo, 2024)
Introduction: The anaerobic threshold (AT), determined by the direct blood lactate measurement, is of huge practical significance during the training test with the aim to estimate the training status of the female athletes. Aim: The aim of this research was to determine anaerobic threshold by direct blood lactate. Material and Methods: Academic research included 20 female subjects divided into four groups: I group - 10 non-trained subjects, who were not previously subjected to the warm up protocol, II group - 10 well-trained subjects who were not previously subjected to the warm up protocol of Conconi test. Results: Results obtained and presented in this paper show that AT, determined by the direct blood lactate measurement, is statistically significant (p < 0,001) in higher values of the heart rate in well-trained subjects compared to the non-trained subjects not subjected. Conclusion: According to the aforementioned authors the Conconi test can be used nonetheless because of its easy administration with the precondition to provide the adequate interpretation in the assessment of the training capability in all sports activities.